An investigation of water usage in casual dining restaurants in Kansas - VanSchenkhof, Matthew (Kansas State University, 2011)
Water is essential for many aspects of daily life including restaurant operations and is necessary for generation and service of properly produced, safe food. However, water is becoming more scarce and expensive due to climate change, infrastructure needs, governmental budget constraints, and shifting water sources. The purpose of this study was to develop benchmarks for water usage and costs for casual dining restaurants (CDRs) in Kansas and identify demographics that may impact water usage and costs. The population for the study was the 952 CDRs in Kansas. Stratified random sampling selected 60 restaurants from five Kansas demographic regions. Data were collected from the local municipal water utilities, Kansas Department of Revenue, Google’s Place Page, and through telephone or on-site interviews with a manager. Results for 221 of 300 (74%) CDRs that responded indicated that on average 1,766 gallons of water were used each day per restaurant, 12.79 per gallons per day for each seat, 68 gallons per employee, and 0.73 gallons per interior square foot. These results were as much as 69% lower than those from a 2000 study conducted by Dziegielewski et al. Significant demographics that impacted water consumption were season of year, population (F= 9.763, p≤.001), menu (F= 2.921, p≤.035), type of ownership (F= 56.565, p≤.000), water source (F= 10.751, p≤.032), irrigation (F= 46.514, p≤.001) and days open (F= 6.085, p≤.000). A stepwise linear regression model (F= 33.676, p≤.000) found ownership (β= -.329, p ≤ 0.000), irrigation (β= -.290, p ≤ 0.000), and population (β= -.176, p ≤ 0.003) impacted water consumption. For water costs, CDRs paid an average of $6.54 per 1,000 gallons of water consumed and had mean annual expenses of $5,026 on revenues of $2,554,254 which was the equivalent of a water cost percent of 0.42. Demographics that impacted water costs were season of year, region (F = 3.167, p≤ 0.015), and water source (F = 4.692, p≤ 0.032). However, a stepwise linear regression model (F= 4.485, p ≤ 0.036) found only water source (β= -.152, p ≤ 0.036) was an indicator of the percentage of revenues related to cost of water. This study did identify benchmarks for water consumption and water costs that can be used in the future by restaurateurs. The primary limitations of the study were that results can only be generalized to casual dining restaurants in Kansas. Future studies can be conducted with different types of restaurants in Kansas and with CDRs in other areas.
Keywords: Casual dining; Water consumption; Water benchmark; Business (0310); Environmental economics (0438); Sustainability (0640)